INSTITUTIONALIZING ASSISTANCE TO RETURNING MIGRANTS LESSONS LEARNED FROM THE ALBANIAN EXPERIENCE - Grazhdani, Teuta (European Scientific Journal, ESJ, 2013)
Return migration is increasingly becoming important for Albania, because of its size and the socio-economic impact it has on the individual, the family, and the community of return. In particular, the successful reintegration of returnees represents a key aspect of the Albanian migration management policy, and hence, an important element of the Albania’ negotiation process for future membership in the European Union (EU). The latter is highly interested on sustainable return, in particular of those who have been irregularly entering and staying in the EU. The successful reintegration has two interrelated dimensions, the personal success, entailing social and economic security for the returnee as an individual, and the contribution of return to the economic and social development of the country of origin. If the return process contributes to both dimensions, it promotes further return in the future and hence more development for local communities. Yet, in practice return migration does not automatically translates into more personal and community prosperity. The paper argues that reintegration is a highly challenging process which requires strong national and local capacities to deliver services and to harness the development impact of return migration. It should consider satisfaction of migrants’ needs in each of the phases of their return process, as well as the needs and potentials of communities of return. This paper’ analysis is based on qualitative methods of research, consisting primarily of document reviews and content analysis of primary and secondary data in the area of return migration and reintegration in Albania.